Police deranged for orchestra [compact disc] - Copeland, Stewart; Sabal-Lecco, Armand; Anderson, Rusty; Keys, Amy; Helene, Carmel; Támar, Ashley; Outwater, Edwin (BMG Rights Management (US), 2023)
The album revisits Police hits newly arranged for full orchestra alongside bassist Armand Sabal Lecco (Paul Simon), guitarist Rusty Anderson (Paul McCartney), and vocalists Amy Keys, Carmel Helene, and Ashley Támar. Percussion and drums were arranged, orchestrated, and co-produced by Copeland.